The Use of Ribosomal RNA as a Microbial Source Tracking Target Highlights the Assay Host-Specificity Requirement in Water Quality Assessments - Rytkönen, Annastiina; Tiwari, Ananda; Hokajärvi, Anna-Maria; Uusheimo, Sari; Vepsäläinen, Asko; Tulonen, Tiina; Pitkänen, Tarja (Frontiers in Microbiology, 2021)
For microbial source tracking (MST), 16S ribosomal RNA gene (rDNA) of host-specific bacteria and mitochondrial DNA (mtDNA) of animal species, known to cause fecal contamination of water, have been commonly used as molecular targets. However, low levels of contamination might remain undetected by using these DNA-based qPCR assays. The high copy numbers of ribosomal RNA (rRNA) could offer a solution for such applications of MST. This study compared the performance of eight MST assays: GenBac3 (general Bacteroidales), HF183 (human), BacCan (dog), Rum-2-Bac (ruminant), Pig-2-Bac (swine), Gull4 (gull), GFD, and Av4143(birds) between rRNA-based and rDNA-based approaches. Three mtDNA-based approaches were tested: DogND5, SheepCytB and HorseCytB. A total of 151 animal fecal samples and eight municipal sewage samples from four regions of Finland were collected for the marker evaluation. The usability of these markers was tested by using a total of 95 surface water samples with unknown pollution load. Overall, performance (specificity, sensitivity, and accuracy) of mtDNA-based assays was excellent (95-100 %), but these markers were very seldomly detected from the tested surface water samples. The rRNA template increased the sensitivity of assays in comparison to the rDNA template. All rRNA-based assays (except Av4143) had more than 80 % sensitivity. In contrast, only half (HF183, Rum-2-Bac, Pig-2-Bac and Gull4) of rDNA-based assays reached this value. For markers targeted to bird feces, the use of rRNA-based assay increased or at least did not change the performance. Regarding specificity, all the assays had >95% specificity with DNA template, except BacCan assay (71%). While using RNA template for the assays, HF183 and BacCan exhibited only a low level of specificity (54% and 55%, respectively). Further, HF183 assay amplified from multiple non-targeted animal fecal samples with RNA template and the marker showed cross-amplification with DNA template too. This study recommends using the rRNA-based approach for MST assays targeting bird fecal contamination. In case of mammal-specific MST assays, the use of rRNA template increases the sensitivity but may reduce the specificity and accuracy of the assay. The finding of increased sensitivity calls for a further need to develop better rRNA-based approaches to reach the required assay performance.